Duplex coatings of cerium and epoxy modified with polypyrrole and silver nanoparticles formed onto AZ91D Mg alloy - Loperena, Ana Paula (2022)
Due to their biocompatibility, biodegradability and mechanical characteristics similar to those of human bone, Mg alloys are a promising alternative as materials for the fabrication of temporary implants. However, its high rate of degradation in a physiological environment prevents their use in these applications. In order to increase the corrosion resistance of the Mg AZ91D alloy in a simulated physiological environment, double cerium and modified epoxy coatings were generated. As a first step, polypyrrole (PPy) modified with silver nanoparticles was chemically synthesized from pyrrole (Py), Ag-NO3 and Ce(SO4)2. Two sizes of nanoparticles were synthesized by varying the concentration of AgNO3 used for the synthesis of the powders. It was verified that the compounds have bactericidal properties against the Gram negative Escherichia coli (E. coli). From these results, a duplex coating was formed onto the AZ91D Mg alloy and then it was modified with the synthesized powders. The coating consisted of an inner cerium-based film and an epoxy film on top, 1 wt.% of the bactericidal composites was added to the resin before its application. Electrochemical analysis as anodic polarization, Tafel polarization curves, variation of the open circuit potential (OCP) and electrochemical impedance spec-troscopy (EIS) verified that the modified coatings were able to protect the alloy against corrosion in simulated physiological solution. The attained protection degree is attributed to the anticorrosive properties of both films and to the presence of polypyrrole (PPy) in the composite, which contributes to maintain the alloy in the passive state. At the same time, the addition of the composite confers antibacterial properties to the coating, which were evaluated through the Kirby-Bauer technique against bacteria E. coli.